Stroke associated pneumonia (SAP) among acute ischaemic stroke patients in Hospital Universiti Sains Malaysia : associated factors and clinical outcomes - Rahman, Sharifah Nursamihah Syed Abd (2021)
Background: Stroke-associated pneumonia (SAP) is associated with adverse clinical outcomes which increase the cost of hospitalisation. There are various factors that contribute to SAP among acute ischaemic stroke patients. However, data on SAP in our population are scarce. Hence, a study to determine the proportion and associated factors of SAP and its clinical outcomes is conducted and it is hoped that the findings of this study could guide future management of patient. Method: A cross-sectional study among acute ischaemic stroke patients who were admitted to Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan between January 2016 until December 2020, were studied. Systematic sampling method were used to select the patient. Variables collected were demograhics, comorbidities, clinical presentations, treatment of SAP and clinical outcomes. These variables were then analysed using descriptive, simple and multiple logistic regression for any significant associations. Results: 446 subjects with acute ischaemic stroke were selected in this study. Proportion of SAP is 22.9% (n=102). Significant independent associated factors for SAP are coronary artery disease (CAD) (OR 2.27, 95% CI (1.12,4.68), p = 0.024), high random blood glucose on admission (OR 1.152, 95% CI (1.081,1.23), p<0.001), nasogastric tube feeding (OR 4.04, 95% CI (1.91,8.56), p<0.001) and high A2DS2 score (OR 1.58, 95% CI (1.35,1.85), p<0.001). For the clinical outcomes, SAP has significant association with all outcomes that were studied; organ impairments (e.g. septic shock, acute kidney injury (AKI), liver dysfunction, respiratory failure, tracheal intubation, need of trachesotomy), recurrent hospital acquired infection (HAP), prolonged hospital stays, higher Modified Rankin Scale (MRS) score on discharge and inpatient mortality, p< 0.05. Conclusion: The significant independent associated factors for developing SAP are CAD, high random blood glucose on admission, nasogastric tube feeding and high A2DS2 score. SAP is significantly associated with adverse outcomes which are organ impairments, recurrent HAP, prolonged hospital stays, poor MRS score on discharge and inpatient mortality. Thus, preventive measure of these significant associated factors needs to be done to reduce incidence of SAP.